2020
DOI: 10.1111/jce.14355
|View full text |Cite
|
Sign up to set email alerts
|

Role of inducibility and its dynamic change in the outcome of catheter ablation of atrial fibrillation: a single center prospective study

Abstract: Background The role of atrial arrhythmia inducibility as an endpoint of catheter ablation of atrial fibrillation (AF) has been a controversial subject in many studies. Our goal is to evaluate the significance of inducibility, the impact of multiple sites or protocols of stimulation or the change in inducibility status in a prospective study including patients with AF undergoing first catheter ablation. Methods We studied 170 consecutive patients with AF (62.9% paroxysmal) undergoing catheter ablation. All pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…7 Studies have evaluated the use of different endpoints immediately after catheter ablation for predicting durable PVI and the likelihood of future arrhythmias with mixed results. 19–28 In the largest randomized study to date, techniques such as waiting for 30 minutes, using adenosine triphosphate to facilitate PV reconnection, or the combination of waiting and using adenosine were not superior to no testing for predicting durable pulmonary vein isolation or reduction in future arrhythmias. Although noninducibility remains important in determining whether ablation for paroxysmal SVT has been successful, noninducibility after AF ablation or termination of AF with ablation have had mixed results for predicting the likelihood of future recurrence.…”
Section: Rhythm Controlmentioning
confidence: 97%
See 3 more Smart Citations
“…7 Studies have evaluated the use of different endpoints immediately after catheter ablation for predicting durable PVI and the likelihood of future arrhythmias with mixed results. 19–28 In the largest randomized study to date, techniques such as waiting for 30 minutes, using adenosine triphosphate to facilitate PV reconnection, or the combination of waiting and using adenosine were not superior to no testing for predicting durable pulmonary vein isolation or reduction in future arrhythmias. Although noninducibility remains important in determining whether ablation for paroxysmal SVT has been successful, noninducibility after AF ablation or termination of AF with ablation have had mixed results for predicting the likelihood of future recurrence.…”
Section: Rhythm Controlmentioning
confidence: 97%
“…8–18 Although achieving durable pulmonary vein ablation in patients with AF has been associated with less recurrent arrhythmias, other endpoints, such as termination of F and noninducibility, have not been associated with improved outcomes. 19–28 Significant complications of AF ablation include stroke and TIAs, pericardial effusion, and vascular complications. 16 The most serious complication that occurs after the ablation procedure is development of an esophageal atrial fistula, although other complications, such as PV stenosis can occur.…”
Section: Rhythm Controlmentioning
confidence: 99%
See 2 more Smart Citations
“…Fifteen studies seemed relevant according to title and abstract and were assessed for eligibility. One of the studies was excluded as no follow‐up was reported 22 and three because different additional ablation strategies were employed 23–25 . After exclusion of ineligible studies, eleven trials with 1544 patients were used for further analysis.…”
Section: Resultsmentioning
confidence: 99%